Structure and Function of the Campylobacter jejuni Chromosome Replication Origin - Jaworski, Pawel; Donczew, Rafal; Mielke, Thorsten; Weigel, Christoph; Stingl, Kerstin; Zawilak-Pawlik, Anna (Frontiers in Microbiology, 2018)
Campylobacter jejuni is the leading bacterial cause of foodborne infections worldwide. However, our understanding of its cell cycle is poor. We identified the probable C. jejuni origin of replication (oriC) – a key element for initiation of chromosome replication, which is also important for chromosome structure, maintenance and dynamics. The herein characterized C. jejuni oriC is monopartite and contains i.) the DnaA box cluster, ii.) the DnaA-dependent DNA unwinding element (DUE) and iii.) binding sites for regulatory proteins. The cluster of five DnaA boxes and the DUE were found in the dnaA-dnaN intergenic region. Binding of DnaA to this cluster of DnaA-boxes enabled unwinding of the DUE in vitro. However, it was not sufficient to sustain replication of minichromosomes, unless the cluster was extended by additional DnaA boxes located in the 3’ end of dnaA. This suggests, despite putative minor differences between minichromosome and chromosome replication, that C. jejuni oriC requires these boxes to initiate or to regulate replication of its chromosome. However, further detailed mutagenesis is required to confirm the role of these two boxes in initiation of C. jejuni chromosome replication and thus to confirm partial localization of C. jejuni oriC within a coding region, which has not been reported thus far for any bacterial oriC.is the first bacterial origin extending into a coding region. In vitro DUE unwinding by DnaA was inhibited by Cj1509, an orphan response regulator and a homologue of HP1021, that has been previously shown to inhibit replication in Helicobacter pylori. Thus, Cj1509 might play a similar role as a regulator of C. jejuni chromosome replication. This is the first systematic analysis of chromosome replication initiation in C. jejuni, and we expect that these studies will provide a basis for future research examining the structure and dynamics of the C. jejuni chromosome, which will be crucial for understanding the pathogens’ life cycle and virulence.